262 INTERLEUKIN-6 IN HUMAN RENAL PROXIMAL TUBULAR CELL DAMAGE IN COLD STORAGE AND REWARMING AND IN TRANSPLANTATION. (1st January 2005) - Jenkins, J. K.; Yacob, G.; Johnson, C.; Salahudeen, A. K.
Abstract : Purpose: To examine the role of potentially harmful cytokines, specifically IL-6, in renal damage that occurs during cold storage and rewarming of kidneys or tubular cells in vitro or immediately after kidney transplantation. Methods: The in vitro model of renal cell injury used RPTE cells stored in University of Wisconsin solution (UW) at 4°C and returned to 37°C in standard conditions, mimicking the storage of cadaveric kidneys. To examine the effect of cytokines on RPTE cells, human TNF-α, IL-1α and -β, and IL-6 were used at 10 ng/mL. Cell injury was measured by LDH release. A Furth-Wistar rat in vivo renal injury model was used and is similar to the manner in which human kidneys are transplanted, using 24 hr of cold storage in UW. Rat IL-6 was measured by sandwich enzyme linked immunsorbent assay in the serum and urine of native and transplanted kidneys and from an effluent from the kidneys prior to and after cold storage. Results: Using a TransSignal RayBio Human Cytokine Antibody Array-3 to screen for inflammatory mediator production, we found that IL-6 was present in small amounts in normally cultured cells and significantly upregulated at 24 hr after 24 hr of cold storage of RPTE cells. IL-8 and MCP-1 were moderately upregulated, and VEGF and IL-15 were slightly uprgulated. We focused on IL-6 because of its apparent constitutive production, significant upregulation, and potentially harmful effects. IL-6 has not previously been reported to be produced from renal tubular cells. Using typical inducers of IL-6, IL-1α/β was found to be the best inducer of IL-6 in RPTE cells. Large amounts were also induced by bacterial lipopolysaccharide (1 μg/mL), TNF-α, and phorbol ester (10 ng/mL) with a calcium ionophore (A23187, 100 ng/mL). In in vitro cell injury experiments RPTE cells cold stored and returned to normal 37°C culture conditions produced large amounts of IL-6 24 to 48 hrs later, as identified on the cytokine array. By LDH release, IL-6 did not induce cell death at 37°C but did greatly enhanced cold-rewarming induced cell death. Deferoxamine, an antioxidant that protects these cells from cold-rewarming injury, slightly reduced basal RPTE cell IL-6, but not cold-rewarming induced IL-6. In two in vivo rat transplant experiments, we have found that the urine or ex vivo effluent from a transplanted kidney produced more IL-6 than the native kidney. Conclusions: RPTE cells have the ability to produce IL-6 in relatively large amounts. Rewarming renal tubular cells after cold storage and reperfusion of a cold stored rat kidney by transplantation also induces IL-6. We conclude that local IL-6 production may play a role in renal damage after cold storage.